Immunogenicity of somatic mutations in human gastrointestinal cancers - Tran, Eric (Science, 2015)
It is unknown whether the human immune system frequently mounts a T cell response against mutations expressed by common epithelial cancers. Using a next-generation sequencing approach combined with high-throughput immunologic screening, we demonstrated that tumor-infiltrating lymphocytes (TILs) from 9 out of 10 patients with metastatic gastrointestinal cancers contained CD4(+) and/or CD8(+) Tcells that recognized one to three neo-epitopes derived from somatic mutations expressed by the patient’s own tumor. There were no immunogenic epitopes shared between these patients. However, we identified in one patient a human leukocyte antigen–C*08:02–restricted T cell receptor from CD8(+) TILs that targeted the KRAS(G12D) hotspot driver mutation found in many human cancers. Thus, a high frequency of patients with common gastrointestinal cancers harbor immunogenic mutations that can potentially be exploited for the development of highly personalized immunotherapies.